Figure 3 from: Costa AF, Siciliano S, Emin-Lima R, Martins BML, Sousa MEM, Giarrizzo T, Silva Júnior JS (2017) Stranding survey as a framework to investigate rare cetacean records of the north and north-eastern Brazilian coasts. ZooKeys 688: 111-134. https://doi.org/10.3897/zookeys.688.12636 - Costa, Alexandra Fernandes; Siciliano, Salvatore; Emin-Lima, Renata; Martins, Bruna Maria Lima; Sousa, Maura Elisabeth Moraes; Giarrizzo, Tommaso; Silva Júnior, José de Sousa e (Zenodo, 2017)
Figure 3 - Stranding events: sperm whales. a Sperm whale Physeter macrocephalus (MPEG 42166) stranded at Praia do Crispim, Marapanim municipality (0°34.8'S, 47°38.4'W) eastern coast of Pará state few hours after death (photo by A.F. Costa) b The same specimen (MPEG 42166) still alive with local people trying to help (internet file) c A newborn Sperm whale (MPEG 42178) stranded at the east coast of Marajó island, Praia do Camburupy (0°32.4'S, 48°28.2'W) on 2014, note the absence of teeth characteristic of a very young specimen (photo by A.F. Costa) d A female Sperm whale (MPEG 42088) stranded at Praia da Pedra do Sal, Parnaíba municipality, Piauí state coastline (2°49.8'S, 41°41.4'W) on 2010 (photo by A.F. Costa).